The Effect of Internet-Based Learning Media on High School Student Achievement - Gustami, Santi Ade (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2020)
Along with the development of a very rapid era, especially in countries that have developed such as America, Europe, Japan and others. These countries are countries that have advanced in the field of technology, technology has a very important role in human life because with the existence of technology humans can easily relate to one another. Now technology is increasingly sophisticated, the most popular technology today is the internet because with the internet there is a lot of valuable information that we can easily retrieve, the internet is one of the very fast and inexpensive communication tools. The internet is a large library in which there are millions of billions of behaviors. information in the form of text in the form of electronic media besides the internet is known as cyberspace, because almost all aspects of life in the real world are on the internet such as sports, politics, entertainment and so forth, besides that the internet also has a very important role in the world of education because of the existence the internet can add to our knowledge and can increase student motivation. With the use of the internet in the world of education so that students can have a commitment to actively learn and have technical abilities, especially in the field of education, therefore the internet can facilitate teaching and learning well. With the use of the internet in the world of education so that students can have a commitment to actively learn and have technical abilities, especially in the field of education, therefore the internet can facilitate teaching and learning well.Keywords: Internet, Learning media, Achievement